Variations in atrial fibrillation screening after ischemic stroke or transient ischemic attack in Sweden. (3rd October 2022) - Straat, K; Wester, P; Svennberg, E; Anggardh Rooth, E; Laska, A C; Asberg, S; Engdahl, J
Abstract: Background/Introduction: The risk of recurrent stroke and mortality is high among patients with ischemic stroke or transient ischemic attack (TIA) and untreated atrial fibrillation (AF). Hence, AF screening after an event has high priority in national and international guidelines. Despite the abundance of evidence on AF detection using different AF screening modalities, there is still no evidence on a prognostic benefit of ECG monitoring post ischemic stroke. There is a risk for variations in clinical practice for AF screening after ischemic cerebrovascular events due to this gap of evidence. Purpose: The aim of this study was to investigate the clinical practice of AF screening after TIA or ischemic stroke at Swedish stroke units. Methods: In collaboration with the stakeholders of the Swedish stroke register (Riksstroke) important fields to study were identified, e.g. AF screening method, first choice of method (multiple answers possible), monitoring duration, clinical follow-up etc. A draft for a digital survey was constructed and then tested and revised by 5 stroke consultants. The survey consisted of 18 multiple choice questions with free text comments and was sent by e-mail to the medical supervisors at all stroke units in Sweden in November 2021. Results: All 72 stroke units in Sweden responded to the survey. Almost all (69/72) stroke units reported that ≥75% of ischemic stroke patients are screened for AF. Of the stroke units 81% had inpatient telemetry as their first choice of AF screening method (Figure 1), but 7% had no access to inpatient telemetry. In case of inpatient telemetry, 30% reported 0–24 hours and 54% reported 24–48 hours as their standard monitoring time. Most had the attending physician at the stroke unit as the primary ECG reader, some with access to support from cardiologist. Different standard monitoring durations for Holter were used (Figure 2) and 17% reported Holter as their first choice of AF screening method. Approximately 85% reported repeated ECG monitoring if high suspicion of cardiac embolization, preferably with repeated Holter (73%) or handheld ECG (49%). Implantable loop recorder (6%), event loop recorder (14%) and 2 weeks registration with ECG-patch (3%) was more infrequently used for this purpose. Conclusions: Clinical practice for AF screening after ischemic stroke or TIA at Swedish stroke units showed considerable variations with a range of different AF screening methods and monitoring durations. Further, the standards and quality of inpatient ECG monitoring is unknown. There is an urgent need for evidence and evidence-based recommendations in this field, the present situation also implies inequality in care. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Stiftelsen Hjartat